Design of Blockchain Technology-based Transcript and Analyzing Management Model for International Students - Dong Ge; Tianyu Wang; Wei Lin; Wei Chen; Jian Chen (My University, 2022)
With globalization, asymmetric information among international students’ academic performance and qualifications, lack information transparency, bloated management bodies, high verification costs, and difficulties in fraud risk management are currently limiting the advancement of internationalization and standardization. These risks and problems also raise questions about the development of IT systems in the education administration and industry as well. Thus, by combining the study of international students’ study results and academic records, we design a blockchain-based study transcript and academic information system concept and architecture with the use of blockchain technology. The result helps to develop business models and authentication features in related fields, set up a rigorous environment, optimize existing processes and rules, and lay a technical and data foundation for the development of international students’ study transcripts and academic authentication.
Keywords: Blockchain Technology Applications and Security; Advanced Technologies in Various Fields